Menakar makna mutu: studi kualitatif atas paradigma manajemen pendidikan islam di tengah arus perubahan - Faiq Julia Iqna’a; Misbahul Arifin (Education Research Center, 2025)
This research focuses on exploring the quality management paradigm in Islamic education amidst social, cultural, and institutional changes. The background to this study is based on the fact that many Islamic educational institutions, particularly Islamic boarding schools (pesantren), face challenges in defining and implementing quality systematically amidst the continued dominance of traditional values. Using a qualitative, phenomenological approach, this research was conducted at Madrasah Diniyah Raudlatul Ulum, Situbondo, East Java. Data collection techniques included in-depth interviews, participant observation, and documentation studies, which were then analyzed using the Miles and Huberman model. The results reveal a tension between the traditional quality paradigm, based on spirituality and adab (ethics) and the systemic approach based on formal measurement and administrative indicators. The charismatic leadership of Islamic boarding schools plays a key role in determining the direction of quality transformation, while local social and cultural dynamics often contribute to resistance to the implementation of formal quality systems. These findings demonstrate that quality management in Islamic education is not merely a technical issue but also a matter of values, meaning, and context. The implications of this research point to the need to develop a quality management model based on local culture and values ​​that can bridge traditional and modern approaches harmoniously and contextually.